The impact of R&D expenditure on productivity in the manufacturing industry in Poland - Roszko-Wójtowicz, Elżbieta; Grzelak, Maria M.; Laskowska, Iwona (Wpływ nakładów na działalność badawczo-rozwojową na wydajność w przemyśle przetwórczym w Polsce, 2019)
EU strategy documents, including the Europe 2020 Strategy, emphasise the priority role of industry in the growth of EU economies. The aim of the presented research is to measure and assess the impact of expenditure on research and development (R&D) activities on the competitiveness of manufacturing divisions in Poland. Labour productivity, expressed as (1) a quotient of gross value added and employment, and (2) a quotient of sold production and employment in the analysed manufacturing divisions, was adopted as the measure of competitiveness. The empirical part of the paper is based on data published by the Central Statistical Office. The analysis covers the period 2009-2017 and provides a contribution to determining the role and importance of research and development as well as innovative activities in shaping competitive advantages of manufacturing enterprises. The obtained results for panel models confirm that R&D expenditure is a secondary factor in changes occurring in the Polish manufacturing industry
Econometrics = Ekonometria, 2019, Vol. 23, No. 4, s. 112-126
Keywords: R&D expenditures; competitiveness; manufacturing; static panel models; nakłady na B+R; konkurencyjność; przetwórstwo przemysłowe; statyczne modele panelowe; dynamiczne modele panelowe